Tumour-infiltrating lymphocytes (TILs) and BRCA-like status in stage III breast cancer patients randomised to adjuvant intensified platinum-based chemotherapy versus conventional chemotherapy. (March 2020) - de Boo, Leonora; Cimino-Mathews, Ashley; Lubeck, Yoni; Daletzakis, Antonios; Opdam, Mark; Sanders, Joyce; Hooijberg, Erik; van Rossum, Annelot; Loncova, Zuzana; Rieder, Dietmar; Trajanoski, Zlatko; Vollebergh, Marieke; et al.
Abstract: Background: The prognostic value of tumour-infiltrating lymphocytes (TILs) differs by breast cancer (BC) subtype. The aim of this study was to evaluate TILs in stage III BC in the context of BRCA1 /2-like phenotypes and association with outcome and benefit of intensified platinum-based chemotherapy. Patients and methods: Patients participated in a randomised controlled trial of adjuvant intensified platinum-based chemotherapy versus conventional anthracycline-based chemotherapy carried out between 1993 and 1999 in stage III BC. Stromal TILs were scored according to International guidelines in these human epidermal growth factor receptor 2 (HER2)-negative tumours. BRCA -profiles were determined using Comparative Genomic Hybridization. Results: TIL levels were evaluated in 248 BCs. High TILs were associated with Triple Negative BC (TNBC). BRCA -like tumours harboured higher TILs compared to non- BRCA -like tumours (median TILs of 20% versus 10%, p < 0.01). TIL levels in BRCA1 -like tumours were higher compared to BRCA2 -like tumours (median TILs of 20% versus 10%, p < 0.001). These correlations remained significant within the oestrogen (ER)-positive subgroup, however not within the TNBC subgroup. In this stage III BC cohort, high TIL level was associated with favourable outcome (TILs per 10% increment, recurrence-free survival (RFS): multivariate hazard ratio ( HR ) 0.82, 95% confidence interval (CI) 0.71–0.94, p  = 0.01; overall survival (OS): multivariate HR 0.80, 95% CI 0.68–0.94, p = 0.01). There was no significant interaction between TILs and benefit of intensified platinum-based chemotherapy. Conclusion: In this high-risk breast cancer cohort, high TILs were associated with TNBC and BRCA1 -like status. Within the ER-positive subgroup, TIL levels were higher in BRCA1 -like compared to BRCA2 -like tumours. When adjusted for clinical characteristics, TILs were significantly associated with a more favourable outcome in stage III BC patients. Highlights: High TILs are significantly associated with TNBC and BRCA1 -like breast tumours. In TNBC, TIL levels are similar in BRCA -like versus non- BRCA -like tumours. In ER-positive BCs, BRCA1 -like tumours harbour more TILs compared to BRCA2 -like tumours. In stage III BC, high TILs are associated with a favourable outcome. TILs are not associated with benefit of intensified platinum-based chemotherapy in this cohort.